Postexercise Hypotension Is Delayed in Men With Obesity and Hypertension - Jarrett, Catherine L.; Tucker, Wesley J.; Angadi, Siddhartha S.; Gaesser, Glenn A. (Frontiers in Physiology, 2022)
Background: Postexercise hypotension (PEH) can play a major role in the daily blood pressure management among individuals with hypertension. However, there are limited data on PEH in persons with obesity and hypertension, and no PEH data in this population beyond 90 min postexercise. Purpose: The purpose of this study was to determine if PEH could be elicited in men with obesity and hypertension during a 4-h postexercise measurement period. Methods: Seven men (age = 28 ± 4 yr; body mass index = 34.6 ± 4.8 kg/m2; brachial systolic blood pressure (SBP): 139 ± 4 mmHg; brachial diastolic BP (DBP): 80 ± 5 mmHg; central SBP: 125 ± 4 mmHg; central DBP: 81 ± 8 mmHg) performed two exercise sessions on a cycle ergometer, each on a separate day, for 45 min at ~65% VO2max. One exercise session was performed at a cadence of 45 RPM and one at 90 RPM. Blood pressure was monitored with a SunTech Oscar2 ambulatory blood pressure monitor for 4 h after both exercise sessions, and during a time-matched control condition. Results: Both brachial and central SBP were not changed during the first h postexercise but were reduced by ~5-10 mmHg at 2 h and 4 h postexercise (p < 0.05) after both exercise sessions. Brachial and central DBP were elevated by ~5-7 mmHg at 1 h postexercise (p < 0.05) but were ~2-3 mmHg lower compared to control at 4 h postexercise. Mean arterial pressure (MAP) was elevated at 1 h postexercise after both exercise sessions but was ~2-3 mmHg lower compared to control at 2 h, 3 h, and 4 h postexercise. Conclusion: We conclude that PEH is delayed in men with obesity and hypertension, but the magnitude and duration of PEH up to 4 h postexercise is similar to that reported in the literature for men without obesity and hypertension. The PEH is most pronounced for brachial and central SBP and MAP. The virtually identical pattern of PEH after both exercise trials indicates that the delayed PEH is a reproducible finding in men with obesity and hypertension.